Gelastic seizures: a retrospective study in five tertiary hospital centres. Issue 2 (1st June 2020) - Loução de Amorim, Isabel; Pereira, Cristina; Sequeira, João; Rocha, Helena; Peralta, Ana Rita; Rego, Ricardo; Bentes, Carla; Bento, Conceição; Sales, Francisco; Robalo, Conceição; Pimentel, José
ABSTRACT: Aim : This study aimed to characterize, clinically and neurophysiologically, a series of patients with gelastic seizures (GS), including both adults and children. Methods : We retrospectively collected patients with GS from epilepsy clinics of five tertiary hospital centres within a single country. Patients were selected through relatives'/caregivers' descriptions, home video and/or video‐EEG monitoring. GS were identified through ictal semiology. Results : Thirty‐five patients were enrolled; 62.9% had initial GS in infancy, 14.3% in adolescence and 22.8% at adult age. Twenty‐six had abnormal MRI: eight presented with hypothalamic hamartoma (HH) and 16 non‐HH lesions that included different structural aetiologies and genetic, metabolic and immune aetiologies. All patients with HH had their first GS in infancy or adolescence. For the remaining aetiologies, GS started in infancy in 59.3%, in adolescence in 11.1% and at adult age in 29.6%. Video‐EEG data was available for analysis in 11 patients, including seven patients with a non‐HH MRI lesion. The ictal onset topography on scalp video‐EEG was usually concordant with the MRI lesion (in 6/7 patients) and the most frequent ictal onset was fronto‐temporal. In two patients, both video‐EEG and MRI suggested a parietal and occipital epileptogenic zone. Conclusion : Aetiologies and patterns of affected topography unrelated to HH are common in patients with GS, and all age groups may manifest with this type of ictal semiology. This ictal manifestation has no lateralizing value and, despite a clear preponderance for hypothalamic, frontal and temporal lobe origins, other brain areas, namely the parietal and occipital lobes, should be considered.